A new superimposed model of the Tongnanba anticline in northeastern Sichuan and its exploration implications - Zhai, Yonghe; Chen, Zhuxin; Zhang, Yuqing; Su, Nan; Wang, Lining; Ren, Rong; Yang, Geng (Frontiers in Earth Science, 2023)
Understanding the structural style, kinematic process, and timing of superimposed structures worldwide is often difficult due to complex structure deformation process. Fortunately, the newly acquired high-quality seismic reflection data and geological observations covering the Tongnanba anticline provide an excellent chance to characterize such structures. Here, we used geological and seismic data from the Tongnanba region to evaluate the structural style and deformation sequence of Tongnanba anticline. In this regard, we propose a new model of the northeastern Sichuan Basin, which are different from the model that deep structures formed earlier than shallow structures demonstrated by previous studies, and we also discussed the implications of this new model for the deep oil and gas exploration. Compressed by Micangshan and Dabashan thrust belts and controlled by three detachment layers, the Tongnanba anticline shows a complex multi-stage, multi-directional, and multi-level superimposed structure. There were three deformation layers vertically, leading to the multi-level detachment thrust structure style. Specifically, the upper and middle deformation layers were mainly controlled by South Dabashan thrust belt in the early stage, forming long-distance detachment thrust structure extended in the NW-SE direction. A series of pop-up structures propagated toward the upper and middle detachment layers. On the other hand, the lower deformation layer was primarily controlled by the Micangshan thrust belt in the late stage, forming complex basement faults extended in the NE-SW direction, which was consistent with Trishear fault-propagation fold. Along the basement detachment developed multiple branch slopes spread from northeast to southwest. The middle and upper deformation layers was transformed by the basement faults, thus forming the complex superimposed structure of north-south zonation and east-west segmentation at present. It was such complex superimposed structure that control the process of hydrocarbon accumulation and adjustment in each deformation layer, and the deep-ultra-deep ancient oil and gas reservoirs may be worth of exploring.